2017
DOI: 10.1080/10286020.2017.1318852
|View full text |Cite
|
Sign up to set email alerts
|

Tomentodione E, a new sec-pentyl syncarpic acid-based meroterpenoid from the leaves of Rhodomyrtus tomentosa

Abstract: A new meroterpenoid, tomentodione E (1), along with four known ones (2-5) were isolated from the leaves of Rhodomyrtus tomentosa. Their structures were elucidated based on extensive spectroscopic data as well as computational methods. Compound 1 represents the first example of meroterpenoid possessing a sec-pentyl syncarpic acid motif coupled with a caryophyllene. Compounds 1-4 were evaluated for their in vitro antiviral activity against respiratory syncytial virus (RSV) with cytopathic effect (CPE) reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Likewise, various terpenoids such as taraxerol, betulin, botulin-3-acetate, 3 β -acetoxy-11 α -epoxyoleanan-28,13 β -olide, 3 β -acetoxy-12 α -hydroxyoleanan-28,13 β -olide, and 3 β -acetoxy-12-oxo-oleanan-28,13 β -olide were also identified in R. tomentosa stems [7,9]. Recently, numerous terpenoids were reported from R. tomentosa leaves, such as rhodomentones A and B [10], tomentosenol A, 4S-focifolidione, 4R-focifolidione [11], tomentodione E [12], rhodomyrtials A and B, tomentodiones A–D [13], tomentodiones E–G, and tomentodiones H-M [14], and from R. tomentosa root, such as tomentodiones H–M [15].…”
Section: Phytochemical Compositionmentioning
confidence: 99%
“…Likewise, various terpenoids such as taraxerol, betulin, botulin-3-acetate, 3 β -acetoxy-11 α -epoxyoleanan-28,13 β -olide, 3 β -acetoxy-12 α -hydroxyoleanan-28,13 β -olide, and 3 β -acetoxy-12-oxo-oleanan-28,13 β -olide were also identified in R. tomentosa stems [7,9]. Recently, numerous terpenoids were reported from R. tomentosa leaves, such as rhodomentones A and B [10], tomentosenol A, 4S-focifolidione, 4R-focifolidione [11], tomentodione E [12], rhodomyrtials A and B, tomentodiones A–D [13], tomentodiones E–G, and tomentodiones H-M [14], and from R. tomentosa root, such as tomentodiones H–M [15].…”
Section: Phytochemical Compositionmentioning
confidence: 99%
“…In addition, its fruits are one of the most popular foods in the wild. The vital medicinal and nutritional properties of R. tomentosa have drawn the attention of researchers in recent years [4,5]. The major chemical components of R. tomentosa include hydrolytic tannins, phloroglucin, flavonoids, and triterpenes [6], which possess antioxidant, anti-inflammatory, anti-tumor, antibacterial and other biological activities [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Myrtucommulones and related acylphloroglucinols from Myrtaceae were evaluated for their in vitro activity against the respiratory syncytial virus (RSV), showing promising effects compared with the ribavirin control. Studies suggested that the antiviral activity of these compounds might be influenced by the side chains of the phloroglucinol moiety [ 20 , 21 ]. Phloroglucinols have also been shown to be effective against other viruses, such as human immunodeficiency virus (HIV), herpes or enterovirus, and preliminary docking analysis data suggest that they can be effective against SARS-CoV-2 [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among these compounds, the myrtucommulones are related to various biological activities. Several have shown significant activities against Epstein–Barr virus (EBV), herpes simplex virus (HSV), respiratory syncytial virus (RSV), and human immunodeficiency virus (HIV), and more recently, docking analysis have suggested that they can be effective against SARS-CoV-2 [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%